Dynamics of Hemostasiogram Parameters in Pregnant Women with Chronic Placental Insufficiency - Homidova Shakhlo Mukhsinovna; Askarova Fotima Kudratovna (Central Asian Journal of Medical and Natural Science, 2023)
In the first multidisciplinary clinic of the Samarkand State Medical University for 2019-2022, a study of hemostasiological parameters of 105 pregnant patients with chronic placental insufficiency was conducted. The patients were divided into two groups depending on the method of treatment - the main group and the comparison group. The study showed positive dynamics of hemostasiogram in patients of the main group after complex treatment with the inclusion of medical ozone and plasmapheresis.